Pengaruh Pendekatan Contextual Teaching and Learning (CTL) untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran IPA di Kelas III SDN 1 Ayong - Potabuga, Fitria K.; Rawis, Joulanda A. M.; Komedien, Brianne E. Jo. (Jurnal Ilmiah Wahana Pendidikan, 2023)
The aim of this research is to determine the improvement in student learning outcomes through the Contextual Teaching and Learning (CTL) approach to the material "Properties of Liquid Objects" in class III of SD Negeri 1 Ayong. This type of research is Classroom Action Research which was carried out over 2 cycles. Each research cycle consists of 4 (four) stages, namely planning, action implementation, observation and reflection with the aim of comparing the values ​​before action and after action. Data collection techniques were carried out using tests, observation sheets of teacher activities and student activities. The research subjects were 14 class III students at SDN 1 Ayong. The data analysis technique used is the percentage calculation data analysis technique. There was an increase in learning outcomes using the Contextual Teaching and Learning (CTL) method on the properties of liquids for class III students at SD Negeri 1 Ayong. This is proven in the increase in scores from the initial test of the 14 students who completed the KKM, there were 6 students or 43% while there were still 8 students or 57% who had not completed it. In Cycle I, of the 14 students who completed it, 8 students or 57% and 6 students who had not completed it, which means 43%. In cycle II, all 14 students completed it or 100%. So it can be concluded that the Contextual Teaching and Learning (CTL) method can improve student learning outcomes in science subjects, especially class III at SD Negeri 1 Ayong.